What is the recursive rule for the sequence?

-7.4, -21.2, -35, -48.8, -62.5

I got an=an+1 -13.8 where a1=-7.4

Partly correct, it should be a(n) = a(n-1) - 13.8, not a(n) = a(n+1) - 13.8

This is because a(n) is given by subtracting 13.8 from the number *before* it, which is a(n-1)

THank you Arora. I guess I need to be more careful with formulas

To find the recursive rule for the given sequence, we need to look for a pattern in the terms of the sequence.

Looking at the sequence: -7.4, -21.2, -35, -48.8, -62.5

We can see that each term is found by subtracting 13.8 from the previous term. For example:
-7.4 + (-13.8) = -21.2
-21.2 + (-13.8) = -35
-35 + (-13.8) = -48.8
-48.8 + (-13.8) = -62.5

So the recursive rule for the sequence can be written as:
an = an-1 - 13.8

Where an represents the nth term in the sequence, and an-1 represents the preceding term.

To summarize, the recursive rule for the given sequence is:
an = an-1 - 13.8, with a1 = -7.4.